ISLAMISASI ILMU PENGETAHUAN PERSPEKTIF ISMAIL RAJI AL-FARUQI DAN IMPLIKASINYA DALAM PENDIDIKAN - Rijal, Syamsul (Fakultas Agama Islam Universitas Islam Madura, 2018)
Muslim intellectual figures argue that the current crisis of modern society is Western education is based on a more materialistic and secularistic view of world, which considers that education is not to make human beings wise, it is to recognize their respective positions in the reality of order and view reality as something that is materially meaningful to humans, and therefore human relations with the reality of reality are exploitative rather than harmonious. This modern humanitarian crisis was criticized by schoolars who later led to the post-modernism. Postmodernism offers a new mind that is tolerant of plurality, demolition and locality. Post-modernism also does not get a way out to unravel the humanitarian crisis. So, many parties try to turn back to religion. One Muslim scholar who was concerned about trying to find a solution to the humanitarian crisis was Ismail Raji al-Faruqi. Al-Faruqi argued that modern knowledge gave rise to contradictions of revelation and reason among Muslims. The Separating thoughts from action, as well as the existence of cultural and religious dualism. Therefore, al-Faruqi argued that the need for Islamization of knowledge and efforts was moving from monotheism. This means that Islamic knowledge always emphasizes the unity of the universe, the unity of truth and knowledge and the unity of life.